Monitoring Urine Bag Berbasis Internet Of Things - Romi Mulyadi; Albirruni Sirregar; Abu Bakar; Yona Ramadika; Vicky Firmansyah (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2025)
During this process of monitoring the contents (volume) of the patient's urinary catheter manually, the nurse must go around one by one to the patient's inpatient room to ensure the contents (volume) of the patient's urinary catheter. This process takes quite a long time while patients who use urinary catheters at the hospital are not small. In addition, if the patient's urinary catheter monitoring process is still done manually, sometimes the medical team or nurses often miss or forget, that the urine bag (catheter) is full. The purpose of this study is to design an Internet Of Things Based Urine Bag Monitoring. The research method used in this study was experimental. The population in this study was 65 TREM study program students with a sample of 40 respondents. Based on the average score table of the Simplicity, Interactivity and Usability surveys. The results of the score calculation using the Likert scale from the Simplicity, Interactivity and Usability factors of urine bag monitoring testing that has been carried out using questionnaires to respondents have shown a high score that is almost close to the value of 5 based on calculations carried out using the Likert scale which indicates that this urine bag monitoring tool can be well received by respondents. It is expected to be developed as material for further research related to monitoring urine bags using applications that can usealarms on users' smartphones and can also use batteries on urine bag monitoring tools